Governance Systemic Foundation and Framework - Türke, Ralf-Eckhard (Contributions to Management Science, 2008)
Instead of yet another theory on good governance, this book presents a substantiation of contemporary notions. It builds on the theoretical foundations for taking an overall perspective on social contexts and culminates in a systemic framework that captures social structures based on first principles of viability and sustainability. The framework at hand enables applicants to view social contexts holistically while at the same time envisioning a rich picture of what leverages the implementation of social purposes beyond the boxes of the professional disciplines: social structures can be assessed, strengths and weaknesses identified and measures arrived at. Ultimately, the required structures can be tailor-made to align forces for a joint implementation of purposes. Conventional static hierarchies can be deployed into dynamic social organisms capable of developing and adapting continuously according to the opportunities and challenges faced.